The β-expansion of the D=1 fermionic spinless Hubbard model off the half-filling regime - Correa Silva, E.V.; Thomaz, M.T.; Rojas, O. (Condensed Matter Physics, 2015)
We obtain that when the spinless model is off the half-filling regime (μ ≠ V), the Helmholtz free energy (HFE) can be written as two β-expansions: one expansion comes from the half-filling configuration and another one that depends on the parameter x = μ - V. We show numerically that the chemical potential as a function of temperature satisfies a relation similar to one derived from the particle-hole symmetry of the fermionic spinless model. We extend the β-expansion of the HFE of the one-dimensional fermionic spinless Hubbard model up to order β⁸. Встановлено, що для безспiнової моделi поза половинним заповненням (µ , V ) вiльну енергiю Гельмгольца можна записати у виглядi двох β-розвинень: одне розвинення походить вiд конфiгурацiї з половинним заповнення, а iнше залежить вiд параметра вiдхилення x = µ − V . Чисельно показано, що
хiмiчний потенцiал як функцiя температури задовольняє спiввiдношення подiбне до того, яке отримується з симетрiї частинка-дiрка фермiонної безспiнової моделi. β-розвинення вiльної енергiї Гельмгольца
одновимiрної фермiонної безспiнової моделi Габбарда продовжено аж до порядку β
⁸
.